Catalytic performance of metal-free ethylenediammonium salt catalysts in the thermal decomposition of ammonium perchlorate - Mei-Qing Lai; Jun Hu; Bo-Wen Fan; Wen-Jing Yang; Jian-Gang Xu; Meng Cui; Guo-Cong Guo (Fuel, 2027)

Palaeoenvironmental evolution and stage-dependent organic matter enrichment in the Late Permian Longtan Formation, Upper Yangtze Block, South China - Hai-Feng Chen; Xin Jin; Marcello Caggiati; Ting-Cong Ren; Bo Luo; Lin-Hao Fang; Hua-Wen Cao; Yang Liu; Chang-Cheng Huang; Bin Xiao; Zi-Han Ma; Hui-Dong Yu; et al. (Sedimentary Geology, 2026)

A novel scattering model for tight-rock reservoirs based on fractal cracks - Rupeng Ma; Jing Ba; José M. Carcione; Cong Luo; Bo Yu; Xiaobin Li; Liwei Song (International Journal of Rock Mechanics and Mining Sciences, 2026)

Bovine-LTID: A vision-based spatio-temporal identity system for multi-camera cattle tracking and long-term behavior monitoring - Boyang Zhao; Bo Xiao; Cong Liu; Xiao Jin; JunMing Ye; Mingjie Yu; Zhenhua Yu (Computers and Electronics in Agriculture, 2026)

Carrier gas dynamics-driven defect engineering of SnO2 thin films formed by powder aerosol deposition for high-performance hydrogen sensing - Yuan-Bo Zhang; Jie Wei; Taek-Kyun Kim; Chulhwan Park; Sang-Mo Koo; Weon Ho Shin; Meng Zhao; Cong Wang; Jong-Min Oh (Chemical Engineering Journal, 2026)

Contrasting urban tree species exhibit site-dependent variation in drought resistance and recovery - Lu Liu; Ji Zheng; Ningxiao Sun; Wen Sun; Jingli Yan; Fuxin Cong; Bo Peng; Xinxin Wang; Shan Yin (Agricultural and Forest Meteorology, 2026)

New insight into the role of lipids in the formation and retention of key aroma compounds in micro-pressure stewed beef based on lipidomics and lipid-derived free radical analysis - Huan Liu; Yu Liu; Xinhe Zhang; Bo Xiao; Pi Li; Peng Gao; Jiangtao Xing; Weiting Wang; Pengfei Du; Jingxian Cong; Chengyu Zeng; Cheng Li; et al. (Food Research International, 2026)

Different drivers of active and inert carbon fraction on forest soil aggregate stability: a functional partitioning approach - Jing Lin; Rui Wang; Miao Xia; Jian-cong Zhang; Peng Qiu; Ke-xin Zhang; Bo Chang; Yu-lin Zhang; Tian-zi Xie; Yi Jian; Jia-yuan Wang; Shan-shan Guo (Journal of Soils and Sediments, 2026)

Plant to carbonate: A microbial bridge for atmospheric CO2 sequestration into soil inorganic carbon revealed by in-situ 13CO2 labeling - Zhihao Zhang; Mengfei Cong; Waqar Islam; Akash Tariq; Bo Zhang; Xudong Wang; Weiqi Wang; Fanjiang Zeng (Biology and Fertility of Soils, 2026)

Multidimensional transcriptomic analysis and in vitro experiments dissect the landscape of 2′,2′,4′,4′-Tetrabromodiphenyl ether in bladder cancer progression - Minghui Sun; Dichao Hu; Tongjie Li; Zeping Chen; Bo Cong; Zhen Xi; Yongchen Wang; Rulin Guo; Jian Zhuo; Wenbo Wu; Haitao Liu (Chemico-Biological Interactions, 2026)

Electrophysiological and Behavioral Responses of Tuta absoluta to the Tomato-Associated Volatile 1-Nonanol - Weifeng Wang; Bo Xu; Xiaolan Ou; Yanhui Lu; Jingsong Kong; Guifen Zhang; Cong Huang; Yibo Zhang; Fanghao Wan (Neotropical Entomology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Expression and ligand-binding characterization of two chemosensory proteins (TabsCSP8 and TabsCSP19) in Tuta absoluta - Bo Xu; Lei He; Yanan Zhou; Xiaobing He; Guohui Zhang; Khalid Haddi; Jordi Riudavets; Judit Arnó; Guifen Zhang; Cong Huang; Yibo Zhang; Fanghao Wan (Pesticide Biochemistry and Physiology, 2026)

Beyond performance-cost trade-off: Engineered Geopolymer Composites (EGC) incorporating ultra-high-volume coal gangue wastes - Zhi-Liang Zhang; Ze-Ming Yang; Ling-Yu Xu; Jian-Cong Lao; Hui Zhang; Yu-Jie Huang; Linghua Shen; Dan-Dan Shi; Bo-Tao Huang (Journal of Cleaner Production, 2026)

Flexible SERS tape: A plasmonic hybrid of AuNPs and layered K2Ti8O17 nanowire network for on-site detection of pesticide residues - Lin Xu; Mingru Cui; Zhongqi Ge; Ruikang Zou; Cong Wang; Pengfei Ni; Xi Huang; Bo Zhong; Lijuan Wang (Analytica Chimica Acta, 2026)

Three-Dimensional Numerical Simulation of Near-Field Hydrodynamic Response and Suspended Sediment Transport Characteristics Around the Caofeidian Port Breakwaters - Yong-Qiang Zhang; Zhe Feng; Cong-Bo Xiong; Wan-Qing Chi; Wan-Jun Zhang (Journal of Marine Science and Engineering, 2026)
Breakwater construction at meso-tidal ports fundamentally alters near-field hydrodynamics and drives harbor sedimentation, yet the three-dimensional mechanisms linking entrance geometry to sediment flux remain poorly quantified. Here, we apply a validated Delft3D tidal–sediment coupled model to Caofeidian Port, Bohai Bay, comparing pre-construction baseline conditions against four entrance width scenarios (400, 300, 250, and 200 m). Breakwater enclosure reduces depth-averaged harbor velocities by 61.9–63.2% during spring tides, while generating tip-jet velocities of 1.41–1.53 m s−1 at the eastern breakwater head—exceeding pre-construction maxima by 14–18%. The eastern tip produces an ebb vortex (radius ~230 m; peak vorticity 0.034 s−1) approximately 34% larger and 62% more intense than its flood counterpart, driving vortex-assisted sediment recirculation toward the harbor interior despite ebb-dominant background velocities. Reynolds flux decomposition confirms that the eastern tip-vortex sector contributes ~39% of net sediment import (advective component: −0.7%), directly quantifying vortex-assisted recirculation as an independent transport mechanism. Bed shear stress falls below the critical erosion threshold (τce = 0.22 Pa) across 76.8% of the harbor area during spring tides (robust lower bound ~60% under wave-coupling correction), creating a structurally stable depositional interior, while the near-entrance zone sustains persistent tidal-cycle resuspension. Asymmetric tidal pumping—flood-phase open-sea SSC of 0.088 kg m−3 versus ebb-phase harbor SSC of 0.032–0.041 kg m−3—drives net spring-tide sediment import of 14.8 × 106 kg per cycle (wave-coupled upper bound: 17.8–19.2 × 106 kg per cycle). Entrance width reduction from 400 to 300 m achieves a favorable sedimentation-to-water exchange trade-off (marginal efficiency ratio 1.23), whereas further reduction to 200 m indicates onset of hydraulic choking. The marginal efficiency ratio declines sharply from 1.23 (400 → 300 m) to 1.03 (300 → 250 m) to 1.01 (250 → 200 m), indicating a hydraulic transition within the 250–300 m range that warrants targeted refinement in future studies.

Identification of novel genes involved in pediatric congenital heart disease using trio-based whole genome sequencing - Bo Wang; Mo Li; Wei Zhou; Huiwen Chen; Ying Xiang; Guocheng Shi; Guoling You; Luan Chen; Yesheng Zhang; Xiaoqing Zhang; Yunqian Gao; Lulu Li; et al. (Science Bulletin, 2026)

Experimental investigation on dynamics and flow resistance of granular-fluid flows - Cong-jiang Li; Yu-xiang Hu; Hong-yu Luo; Jie-yuan Zhang; Hai-Bo Li; Jia-wen Zhou (Engineering Geology, 2026)

Multifunctional carboxymethyl cellulose/polydopamine dual-network conductive hydrogels for motion detection and photothermal therapy - Yiying Wei; Bo Cong; Xiaopu Ji; Dangyang Wang; Jinghui Hu; Zonglei Mou; Haiqing Song; Yue Zhi; Yushu Liu; Guofeng Zhang; Wan Ru Sun; Pingyu Wang; et al. (Carbohydrate Polymers, 2026)

Monosaccharide composition, physicochemical characteristics, and prebiotic activity of purified polysaccharides from red Ganoderma mushroom prepared using ultrasonic-assisted extraction - Bo Jie Chen; Cong Xia; Peiling Wu; Yang Liu; Jing Li; Tiemin Jiang; Xia Li; Biyu Peng; Hock Eng Khoo (Natural Product Research, 2026)

The effects of water depth, temperature and seasonal water-column overturning on sediment-derived odorous volatile organic compounds of a ladder-step reservoir, Yiwu, China - Bo Gao; Junyu Ma; Jiahe Wang; Hongbin Zhu; Yangkang Fang; Qinggang Gong; Zhizheng Luo; Yi He; Rong Zhang; Cancan Jiang; Yongzhi Chi; Yanghui Xiong; et al. (Journal of Environmental Chemical Engineering, 2026)

Ball milling assisted Al/Si co-doping for enhanced performance of calcium-based CO2 adsorbents: Structural evolution and synergistic mechanisms - Penghui Yang; Cong Luo; Huizhe Wu; Zhen Du; Bo Liu; Xiaoshan Li; Fan Wu; Zewu Zhang; Liqi Zhang (Chemical Engineering Journal, 2026)

LncRNA expression signature correlated with cuproptosis: prognostic implications and insights into immune microenvironment in ovarian cancer - Cong-Min Wang; Ya-li Hao; Xiao-Fei Li; Jian-lei Wu; Kai-Kai Hao; Fang Guo; Hai-Bo Zhang (Journal of Molecular Histology, 2026)

SO2 and NO2 removal under ambient conditions by hierarchically porous 2,6-Diaminopyridine mediated Zr-MOF-(OH)2 metal-organic framework - Feng Liu; Chuan Zhou; Yuwei Dai; Bo Yang; Hantong Chen; Qiong Wu; Cong Zhao; Sumin Li; Jian Kang; Pingwei Ye (Chemical Engineering Journal, 2026)

PEDV nonstructural protein 14 inhibits RIPK3 and RIPK1-mediated PANoptosis - Xingyi Xie; Dengkun Wang; Xueke Sun; Xuechen Li; Mengru Luo; Jiahao Cong; Wenju Yuan; Huihui Huang; Zhaojiang Chen; Yuhang Zhang; Zhengjie Kong; Bo Wan (Veterinary Microbiology, 2026)

Coronatine promotes post-harvest softening in ‘Gui Qi’ mango (Mangifera indica L.) through regulation of β-galactosidase and ethylene biosynthesis-related genes - Ziqing Mi; Bilal A. Rather; Hanqing Cong; Yibo Bai; Rongxiang Wang; Bo Zheng; Xuefei Jiang; Pingyin Guan; Fei Qiao (Postharvest Biology and Technology, 2026)

Energy-saving and fire/water-resistant recyclable aerogel coatings for thermal-insulating polyurethane foam - Cong-Mei Lin; Xue-Lian Chen; Fu-Rong Zeng; Li-Xiao Hao; Yu-Shi Wen; Bing-Ru Zhang; Bo-Wen Liu; Lin Zhang; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Experimental study on cavity evolution and pressure characteristics under an unsteady tail jet - Qian Yang; Bo Qin; Minchao Zhou; Xixi Li; Dong Guo; Cong Wang (Ocean Engineering, 2026)

Heavy metal speciation and risk assessment in suspended particulate matter: A case study of small-medium freshwater bodies in Southwestern China - Cong Yao; Zhiyi Dai; Zhijie Shen; Shanyi Tian; Sihua Zhu; Jiacheng Shi; Yuping Xiang; Yongmin Wang; Bo Zhu; Dingyong Wang (Journal of Hazardous Materials, 2026)

Bundle adjustment-based co-registration with high geolocation accuracy for UAV photogrammetry - Nan Jiang; Hai-bo Li; Cong-jiang Li; Yu-xiang Hu; Jia-wen Zhou (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

A carbon sink calculation model for concrete buildings considering time-variant environment - Jia-cheng Xu; Bei Li; Ye Tian; Ruo-yi Zhao; Guo-yi Zhang; Qiang Zeng; Cong-cong Ma; Bo-Tao Huang; Hong-jing Xue; Yun-jian Li; Qing Cai (Environmental Impact Assessment Review, 2026)

A self-adaptive interfacial adhesive strategy for enduring flame retardancy and aging resistance of anti-aging agent-free polyurethane foam - Yan Wang; Lei He; Heng-Fei Liang; Chen Ye; Ze-Yong Zhao; Ming-Jun Chen; Yu-Zhong Wang; Hai-Bo Zhao; Cong Deng (Chemical Engineering Journal, 2026)

Synergistic Zn2+/H+ transport realized by proline-induced hydrogen-bond networks in high-performance MnO2 cathode - Kun Li; Han Zhang; Jianxin Wang; Yongxin Liang; Tiefeng Liu; Shengrong Guo; Zheyu Jin; Zhi Zhang; Chenfeng Guo; Bowen Cong; Bo Wang (Chemical Engineering Journal, 2026)

CuO2-loaded quaternized chitosan-based composite nanofiber membranes: Immediate contact antibacterial for high-risk public surface engineering - Caiyun Chen; Yufei Tang; Cong Wu; Yani Sun; Bo Zhang; Kang Zhao; Zixiang Wu (Chemical Engineering Journal, 2026)

Genome-wide Characterization of Heat Shock Protein (HSP) Genes in Tuta (Phthorimaea) Absoluta: Insights into Thermal Stress Response - Bo Xu; DeYuan Kong; Guohui Zhang; Cong Huang; Guifen Zhang; Fanghao Wan (Neotropical Entomology, 2025)

A binary-medium-based multiscale constitutive model for stabilized expansive soil considering the influence of freeze-thaw cycles - Cong Chen; Yunyong He; Bo Xiang; Enlong Liu; Yanyang Yu (Cold Regions Science and Technology, 2025)

Aqua regia, as a carbon modifier, improves the physical properties and chemical adsorption capacities of activated carbon from passion fruit peel - Bo Jie Chen; Cong Xia; Jie Tang; Xinhong Dong; Jing Li; Xia Li; Biyu Peng; Hock Eng Khoo (Biocatalysis and Agricultural Biotechnology, 2025)

Bisphenol A exposure promotes proliferation and invasion capabilities of bladder cancer cells: Insights from gene expression and pathway analysis - Bo Cong; He Liu; Minghui Sun; Dichao Hu; Tongjie Li; Wenbo Wu; Haitao Liu (Toxicology Letters, 2025)

Real-time prediction of tunnel face deformations by multivariate construction information - Yuxuan Xia; Dongming Zhang; Bo Zhang; Hongwei Huang; Yue Tong; Cong Nie (Tunnelling and Underground Space Technology, 2025)

Electron beam irradiation significantly improves post-harvest fruit quality and shelf-life of Mango (Mangifera indica L.) - Bo Zheng; Muhammad Shahzaib; Ziqing Mi; Xuefei Jiang; Yuandi Zhu; Hanqing Cong; Yerong Wang; Xiaoling Xu; Caihua Liu; Fei Qiao (Postharvest Biology and Technology, 2025)

Overview of Ferroptosis in Cadmium Toxicity - Xinyu Zhang; Zeao Hua; Zhi Lu; Bo Wang; Peilin Wang; Shanshan Zhang; Xu Yang; Cong Zhang (Biological Trace Element Research, 2025)

Efficacy and safety of an mRNA encoding neutralizing antibody against SARS-CoV-2 in non-human primates - Hang Chi; Suo-Qun Zhao; Yun-Peng Liu; Xiao-Chuan Xiong; Xia Zhong; Xing-Xing Suo; Xing-Yao Huang; Can Yue; Jing-Jing Zhang; Zhe Cong; Na Li; Fei-Xue Du; et al. (Science Bulletin, 2025)

Characterization of azadirachtin resistance in a laboratory-selected strain of Drosophila. melanogaster - Kuitun Liu; Cong Rao; Chongwei Li; Wenlin Jiang; Bo Hu; Jianya Su (Pesticide Biochemistry and Physiology, 2025)

Senecavirus A nonstructural protein 3A Inhibits Ago2-mediated RNAi antiviral response - Mengru Luo; Xingyi Xie; Dengkun Wang; Xuechen Li; Xianghui Ling; Wenju Yuan; Jiahao Cong; Huihui Huang; Yuhang Zhang; Zhengjie Kong; Bo Wan (Veterinary Microbiology, 2025)

The stability of plant richness, composition, and cover responds nonlinearly to warming in a decade‐long experiment - Ruonan Shen; Yangjian Zhang; Juntao Zhu; Yunlong He; Zhoutao Zheng; Guang Zhao; Nan Cong; Bo Zhao; Xianzhou Zhang; Lin Jiang; Yann Hautier (Ecology, 2025)
Global warming is expected to change the diversity, composition, and functioning of plant communities. However, it remains unclear how warming alters the temporal stability of different aspects of plant communities and the extent to which these different aspects are interlinked or respond differently to warming. Here, using data from a 10‐year, multi‐level warming experiment in an alpine grassland, we quantified the temporal stability of three plant community aspects—species richness, composition, and cover—in response to warming scenarios that increase soil temperature by 0.4, 1.6, 2.1, and 2.5°C. We found a nonlinear concave stability response to warming for each of the three community aspects investigated. That is, moderate warming caused moderate increases in the stability of richness, composition, and cover, whereas severe warming caused strong decreases in stability. Additionally, we found that the processes contributing to stability differed among the three community aspects, with warming weakening the relationships between them. Severe warming reduced the stability of cover by reducing the stability of dominant species and species asynchrony. Compositional stability decreased due to declines in species richness, species asynchrony, and dominant species stability. Richness stability decreased due to a decline in species richness. Our results demonstrate that the stability of different community aspects responds nonlinearly to future warming scenarios, with moderate warming stabilizing but high‐level warming destabilizing plant species richness, composition, and cover. Our findings emphasize the collective influence of species richness, species asynchrony, and dominant species stability as key factors modulating community stability in the context of global warming.

Expression and sex pheromone-binding characteristics of pheromone-binding protein 3 in Tuta absoluta (Lepidoptera: Gelechiidae) - Xiaolan Ou; Xianya Li; Bo Xu; Yusheng Wang; Guifen Zhang; Wanxue Liu; Fanghao Wan; Hongbo Jiang; Khalid Haddi; Cong Huang; Yibo Zhang (Pesticide Biochemistry and Physiology, 2025)

Modeling growth curves to estimate the suitable slaughter age for the ostriches (Struthio camelus) - Ha Xuan Bo; Han Quang Hanh; Do Thi Hue; Dang Vu Hoa; Nguyen Thi Hoa; Nguyen Thanh Cong; Nguyen Thi Vinh; Dang Thuy Nhung; Do Duc Luc (Tropical Animal Health and Production, 2025)
Using an accurate growth curve to estimate the suitable age for slaughter has many benefits for ostrich farming. This study was carried out to compare eight growth curve models for estimating body weight and monthly gain of ostriches raised in tropical conditions and then suggested the suitable slaughter age for these ostriches. Two hundred eighty-two ostriches (124 males and 158 females) were raised from birth to 12 months of age to measure individual monthly body weight, and the growth data was analyzed by R software. Eight growth functions (von Bertalanffy, Bridges, Janoschek, Gompertz, Logistic, Lopez, Richards, and Weibull) were used to create the growth curves of ostrich. The Weibull function was the best model among 8 tested models to describe the growth of both male and female ostriches, and the monthly gain (MG) reached the maximum at the 6 th month of age. The maximum average monthly gain (AMG) was obtained between the 9 th and 10 th month of age for both males and females. The best-fit model in this study (Weibull function) suggests the suitable slaughter ages were estimated from the 9 th to 10 th month of age for both male and female ostriches, with estimated body weights of 93 kg for male and 90 kg for female.

Spatio-temporal simulation of net ecosystem productivity in the Tibetan Plateau region using multi-scale data assimilation for terrestrial ecosystem process model - Changhui Ma; Si-Bo Duan; Cong Xu; Wenhua Qin; Feng Wang; Lei He (Agricultural and Forest Meteorology, 2025)

Metal covalent organic frameworks-based laccase-like nanozyme for oxidative degradation and identification of phenolic pollutants - Jin Liu; Cong Hu; Xiaoyan Meng; Ying Sun; Bo Zhao; Zian Lin (Journal of Hazardous Materials, 2025)

Green and low-carbon matrices for Engineered/Strain-Hardening Cementitious Composites (ECC/SHCC): Toward sustainable and resilient infrastructure - Ling-Yu Xu; Jing Yu; Bo-Tao Huang; Jian-Cong Lao; Hao-Liang Wu; Xi Jiang; Tian-Yu Xie; Jian-Guo Dai (Journal of Cleaner Production, 2025)

Effects of silymarin supplementation in late pregnancy and lactation on reproductive performance, colostrum quality, blood biochemistry and inflammation levels of sows - Guanglei Cong; Shuangshuang Xia; Chunxue Liu; Junbo Li; Ifen Hung; Lili Zhang; Shuaipeng Guo; Bo Zhao (Tropical Animal Health and Production, 2025)

Influence of Interfacial Properties on Mechanical Behaviors and Failure Patterns of Coal–Measure Thin Interbedded Rocks Under Uniaxial Compression Using 3D FDEM - Richao Cong; Ruiyue Yang; Yiwen Liu; Gensheng Li; Zhongwei Huang; Bo Zhang (Rock Mechanics and Rock Engineering, 2025)

Oxidation mechanism of methane fuel blended with dimethyl ether/hydrogen/ammonia via ReaxFF molecular dynamics simulation - Liang Song; Chun-Chen Xu; Jing Ye; Yong Zhang; Fang-Chao Hou; Bo-Cong Chen; Hao-Long Su; Jing Sun (Fuel, 2025)

Experimental analysis on breaching mechanism of earth-rock dam induced by landslide generated waves - Zhen-han Du; Jia-Wen Zhou; Shi-Chen Zhang; Qi-Ming Zhong; Hai-Bo Li; Yu-Xiang Hu; Cong-Jiang Li; Jie-Yuan Zhang (Engineering Geology, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Contribution of fungal biomass to persistent soil carbon across natural ecosystems - Xiang Wang; Guang-Hui Yu; Yakov Kuzyakov; Bo-Hao Yin; Andreas Kappler; Cong-Qiang Liu (Science China Earth Sciences, 2025)

Climatological Annual Mean and Seasonal Variations in Spatial Energy Spectra of Satellite-Observed Sea-Surface Chlorophyll-a Concentration in the East China Sea - Bo Huang; Yanzhen Gu; Cong Liu; Fangguo Zhai; Shuangyan He; Dan Song; Peiliang Li (Journal of Marine Science and Engineering, 2025)
The hourly L2-level chlorophyll-a (CHL-a) concentration spatial energy spectra of GOCI-II from 2021 to 2023 are employed to investigate the characteristics of the CHL-a spatial energy spectrum slopes in three regions of the East China Sea, namely nearshore, offshore, and open ocean. The seasonal trends of the spatial energy spectrum slopes are also examined for the nearshore and offshore regions. It is observed that the slopes of the CHL-a spatial energy spectrum are −2 at scales larger than 5 km, whereas at smaller scales, they are −5/3, −1, and −0.3 from the nearshore region to the open sea, respectively. On the larger scales, the spatial energy spectrum slopes are consistent with surface quasi-geostrophic (sQG) theory, but this is not the case on smaller scales. An insufficient regional CHL-a concentration leads to a flattening of the slope at the smaller scales. On the submesoscale, the slope of the nearshore CHL-a concentration spatial energy spectrum is steeper in summer and flatter in winter, a pattern that contrasts with changes observed offshore. This seasonal variation is attributed to the southward flow of ZheMin Coastal Current (ZMCC) during winter, which carries freshwater and enhances the horizontal buoyancy gradient in the nearshore region.

Bone marrow mesenchymal stem cell transplantation protects rats from myocardial infarction by regulating TXNIP/NLRP3 pathway-mediated inflammation and fibrosis - JianNan Bai; Cong Wang; HongQiang Yu; QingChao Wang; JinFeng Zhang; DanDan Shao; ZhiQiang Yu; Bo Meng; You Li (Molecular & Cellular Toxicology, 2025)

Rapid and efficient removal of organophosphorus pollutant and recovery of valuable elements: A boosted strategy for eliminating organophosphorus from wastewater - Yujia Xiang; Yang Liu; Boyi Cong; Zhenpeng Cai; Ningruo Wang; Heng Zhang; Chuanshu He; Bo Lai (Water Research, 2024)

Experimental and numerical simulation study on the dissipation mechanism of landslide-generated waves through multiple barrier structures - Yu-xiang Hu; Cong-jiang Li; Hai-bo Li; Da-rui Liu; Jia-wen Zhou (Ocean Engineering, 2024)

The CDK4/6 Inhibitor Palbociclib Induces Cell Senescence of High-grade Serous Ovarian Cancer Through Acetylation of p53 - Cong Ye; Yan Cheng; Xiaohong Qian; Bo Zhong; Jinchun Ma; Hongling Guo (Biochemical Genetics, 2024)

Thermal decomposition behaviors of adamantane and 1-methyladamantane in oxygen atmosphere: ReaxFF molecular dynamics simulation - Liang Song; Tian-Cheng Zhang; Yong Zhang; Bo-Cong Chen; Jing Ye; Fang-Chao Hou; Jing Sun; Su-Qin Zhou (Fuel, 2024)

Experimental Investigation on Hydraulic Fracture Propagation Behaviors of Coal-Measure Thin Interbedded Rocks - Richao Cong; Ruiyue Yang; Meiyang Jing; Gensheng Li; Zhongwei Huang; Bo Zhang (Rock Mechanics and Rock Engineering, 2024)

Pyrolysis and oxidation mechanisms of ethylene and ethanol blended fuel based on ReaxFF molecular dynamics simulation - Liang Song; Chun-Chen Xu; Jing Ye; Yong Zhang; Biao Chen; Fang-Chao Hou; Bo-Cong Chen; Hao-Long Su; Jing Sun (Fuel, 2024)

Effects of Se-enriched yeast on the amelioration of atrazine-induced meat quality degradation - Cong Zhang; Yu Liu; Peilin Wang; Bo Wang; Shanshan Zhang; Zeao Hua; Yanan Li; Xuebing Wang; Xu Yang (Food Chemistry, 2024)

Effects of natural and synthetic antioxidants addition on the characteristic flavor and metabolites of walnut oil during oxidation - Bo-Nan Xi; Jing-Jing Zhang; Cong Li; Xiao Xu; Qin Zeng; Yiran Zhang; Bang Chen; Yehua Shen (Food Bioscience, 2024)

Novel separate aeration self-circulating technology for continuous aerobic granular sludge process: Performance evaluation, hydrodynamic simulation and control strategy - Wei-Kang Qi; Run-Feng Tian; Bo Li; Shu-Jun Zhang; Yong-Zhen Peng; Cong Wang (Water Research, 2024)

Association of prenatal multiple metal exposures with child neurodevelopment at 3 years of age: A prospective birth cohort study - Yun Qiu; Yuxin Liu; Ming Gan; Weiting Wang; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; Xin Xu; et al. (Science of The Total Environment, 2024)

Lipidomics and metabolomics reveal the molecular mechanisms underlying the effect of thermal treatment on composition and oxidative stability of walnut oil - Jing-Jing Zhang; Xiao Xu; Qin Zeng; Cong Li; Bo-Nan Xi; Yu Shu; Tianchen Ma; Hengtao Dong; Yehua Shen (Food Research International, 2024)

An adaptive phase field approach to 3D internal crack growth in rocks - Bin Xu; Tao Xu; Michael J. Heap; Alexandra R.L. Kushnir; Bo-yi Su; Xiao-cong Lan (Computers and Geotechnics, 2024)

Inspection for the desorption effect and mechanism of petroleum from contaminated soil in surfactant solution - Meixia Gu; Xiaoshuang Yin; Xiaoning Feng; Nan Shi; Wei Zhu; Shuhai Guo; Min Li; Bo Wu; Gang Li; Xingshun Cong; Bin Lou; Fushan Wen; et al. (Journal of Soils and Sediments, 2024)

Model Test Study on Response of Weathered Rock Slope to Rainfall Infiltration under Different Conditions - Cong Li; Rongtang Zhang; Jiebing Zhu; Bo Lu; Xiaowei Wang; Fangling Xu; Xiaoke Shen; Jiesheng Liu; Weizhen Cai (Journal of Earth Science, 2024)

Genome-wide analysis of polyphenol oxidase gene family in Solanum tuberosum and functional identification of StuPPO9 in regulating tolerance to Phytophthora infestans - Ming Chi; Da Tang; Cong Xue; Jieping Huang; Bo Liu; Mengqi Cao (Physiological and Molecular Plant Pathology, 2024)

Numerical investigation of mechanical responses and failure features of coal measure strata using combined finite-discrete element method - Richao Cong; Ruiyue Yang; Yanjin Gong; Gensheng Li; Zhongwei Huang; Bo Zhang (Computers and Geotechnics, 2024)

Pilot-scale field studies on activated microbial remediation of petroleum-contaminated soil - Wu-Juan Sun; Qian Li; Bo-Yun Luo; Rui Sun; Cong-Yu Ke; Si-Chang Wang; Qun-Zheng Zhang; Xun-Li Zhang (Environmental Geochemistry and Health, 2024)

Activation of BMP4/SMAD pathway by HIF-1α in hypoxic environment promotes osteogenic differentiation of BMSCs and leads to ectopic bone formation - Cong Chen; Chunhao Song; Bo Liu; Yitao Wang; Jun Jia; Kai Pang; Yuanhao Wang; Peng Wang (Tissue and Cell, 2024)

Excessive climate warming exacerbates nitrogen limitation on microbial metabolism in an alpine meadow of the Tibetan Plateau: Evidence from soil ecoenzymatic stoichiometry - Mengke Cai; Yangjian Zhang; Guang Zhao; Bo Zhao; Nan Cong; Juntao Zhu; Zhoutao Zheng; Wenjuan Wu; Xiaoqing Duan (Science of The Total Environment, 2024)

Pickering extremulsion rich in lipophilic phytochemicals: Preparation, characterization and application - Xu Han; Cong-Jia Duan; Zi-Fei Wei; Jian Xu; Cheng-Dong Nie; Yuan-Hang Chang; Bo-wen Zhai; Yu-Jie Fu (Journal of Food Engineering, 2024)

Corrigendum to “Comparing the mechanisms of two types of summer extreme precipitation in Beijing-Tianjin-Hebei region, China: Insights from circulation patterns and moisture transports” [Atmospheric Research, 302 (2024), 107304] - Jing Cong; Huijun Liu; Guicai Ning; Hong Chen; Xueyan Bi; Bo Liu; Yuanjian Yang; Haiyun Xia (Atmospheric Research, 2024)

Comparing the mechanisms of two types of summer extreme precipitation in Beijing-Tianjin-Hebei region, China: Insights from circulation patterns and moisture transports - Jing Cong; Huijun Liu; Guicai Ning; Hong Chen; Xueyan Bi; Bo Liu; Yuanjian Yang; Haiyun Xia (Atmospheric Research, 2024)

Evolution and adaptation of terrestrial plant‐associated Plantibacter species into remote marine environments - Li Liao; Qilong Qin; Dian Yi; Qiliang Lai; Bolin Cong; Huiming Zhang; Zongze Shao; Jin Zhang; Bo Chen (Molecular Ecology, 2024)
Microbes are thought to be distributed and circulated around the world, but the connection between marine and terrestrial microbiomes remains largely unknown. We use Plantibacter , a representative genus associated with plants, as our research model to investigate the global distribution and adaptation of plant‐related bacteria in plant‐free environments, particularly in the remote Southern Ocean and the deep Atlantic Ocean. The marine isolates and their plant‐associated relatives shared over 98% whole‐genome average nucleotide identity (ANI), indicating recent divergence and ongoing speciation from plant‐related niches to marine environments. Comparative genomics revealed that the marine strains acquired new genes via horizontal gene transfer from non‐ Plantibacter species and refined existing genes through positive selection to improve adaptation to new habitats. Meanwhile, marine strains retained the ability to interact with plants, such as modifying root system architecture and promoting germination. Furthermore, Plantibacter species were found to be widely distributed in marine environments, revealing an unrecognized phenomenon that plant‐associated microbiomes have colonized the ocean, which could serve as a reservoir for plant growth‐promoting microbes. This study demonstrates the presence of an active reservoir of terrestrial plant growth‐promoting bacteria in remote marine systems and advances our understanding of the microbial connections between plant‐associated and plant‐free environments at the genome level.

New fossils reveal the Paleogene establishment of relict Craigia (Malvaceae) in its extant range - Jia Li; Shi-Tao Zhang; Xue-Yan Li; Cong-Li Xu; Yuan Zhu; Ruo-Han Zuo; Lin-Bo Jia (Palaeoworld, 2024)

Fly ash-dominated High-Strength Engineered/Strain-Hardening Geopolymer Composites (HS-EGC/SHGC): Influence of alkalinity and environmental assessment - Jian-Cong Lao; Rui-Yang Ma; Ling-Yu Xu; Yang Li; Yi-Nong Shen; Jie Yao; Yan-Shuai Wang; Tian-Yu Xie; Bo-Tao Huang (Journal of Cleaner Production, 2024)

Crystal mush rejuvenation in the formation of Triassic dacites in Mengku, SE Tibetan Plateau - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; Zai-Bo Sun; Xiao-Chi Liu; De-Feng He; Wei-Qiang Ji; Fang-Yang Hu; Shao-Hua Zhang; Xiao-Ming Huang (Journal of Asian Earth Sciences, 2024)

Cognitive Deficits and Alzheimer’s Disease-Like Pathologies in the Aged Chinese Tree Shrew - Hongli Li; Bo-Lin Xiang; Xiao Li; Cong Li; Yu Li; Ying Miao; Guo-Lan Ma; Yu-Hua Ma; Jia-Qi Chen; Qing-Yu Zhang; Long-Bao Lv; Ping Zheng; et al. (Molecular Neurobiology, 2024)

The pre-corrosion fatigue behavior of 321 steel coated by laser additively manufactured FeCoNiCrMn high-entropy alloy - Wei Li; Shengnan Hu; Shunpeng Zhu; Guowei Bo; Chipeng Zhang; Houjun Qin; Hui Chen; Libo Zhou; Xulong Peng; Jianjun He; Cong Li; Shengde Zhang; et al. (Ocean Engineering, 2024)

Characterization and metabolism pathway of volatile compounds in walnut oil obtained from various ripening stages via HS-GC-IMS and HS-SPME-GC–MS - Bo-Nan Xi; Jing-Jing Zhang; Xiao Xu; Cong Li; Yu Shu; Yu Zhang; Xuanming Shi; Yehua Shen (Food Chemistry, 2024)

Mn-CaCO3-based nanosystem for augmented sonodynamic-chemodynamic immunotherapy via PI3K/Akt signaling pathway - Mashiti Sha; Huansong Li; Yangsui Liu; Cong Tang; Xue Bai; Yun Wang; Bo Yuan; Kairui Liu; Xiaoning Gao; Jun Yan; Silong Wei; Jin Chang; et al. (Chemical Engineering Journal, 2024)

Transcriptomic analysis of ncRNAs and mRNAs interactions during drought stress in switchgrass - Cong Guan; Wei Li; Guoliang Wang; Ruimei Yang; Jinglei Zhang; Jinhong Zhang; Bo Wu; Run Gao; Chunlin Jia (Plant Science, 2024)

Improving enzyme accessibility in the aqueous enzymatic extraction process by microwave-induced porous cell walls to increase oil body and protein yields - Xin Guo; Bi-cong Wu; Yun Jiang; Yu Zhang; Bo Jiao; Qiang Wang (Food Hydrocolloids, 2024)

Review of neurotoxicity of T-2 toxin - Youshuang Wang; Bo Wang; Peilin Wang; Zeao Hua; Shanshan Zhang; Xuebing Wang; Xu Yang; Cong Zhang (Mycotoxin Research, 2024)

Dietary sources of branched-chain fatty acids and their biosynthesis, distribution, and nutritional properties - Huijia Lu; Zhen Wang; Bo Cao; Fang Cong; Xingguo Wang; Wei Wei (Food Chemistry, 2024)

Energy-efficient fluorine-free electro-refining of crude lead in a green methanesulfonic acid system - You-gang Li; Cong Chang; Jun-jie Qu; Chang-liu Xiang; Tao Luo; Shan-shan Liu; Shuai Li; Sheng-hai Yang; Heng-hui Wang; Xiao-bo Min; Chang-hong Wang; Yong-ming Chen (Journal of Environmental Chemical Engineering, 2023)

Mechanism of low-voltage electrostatic fields on the water-holding capacity in frozen beef steak: Insights from myofilament lattice arrays - Yong Xie; Kai Zhou; Bo Chen; Yunhao Ma; Cheng Tang; Peijun Li; Zhaoming Wang; Feiran Xu; Cong Li; Hui Zhou; Baocai Xu (Food Chemistry, 2023)

Effects of pomelo sponge fermented by Monascus ruber on cholesterol metabolism and intestinal microbiota in high-fat diet mice - Yu-Zhen Li; Jie-Yan Shi; Hui Wu; Ka-Hing Wong; Peter C.K. Cheung; Xu-Cong Lv; Qiong-Qiong Yang; Bo-Bo Zhang (Food Bioscience, 2023)

Forgone summertime comfort as a function of avoided electricity use - Minji Kwon; Shuchen Cong; Destenie Nock; Luling Huang; Yueming (Lucy) Qiu; Bo Xing (Energy Policy, 2023)

Effects of biochar additions on the mechanical stability of soil aggregates and their role in the dynamic renewal of aggregates in slope ecological restoration - Mei-hua Sheng; Xiao-yan Ai; Bo-cong Huang; Meng-ke Zhu; Zong-yang Liu; Ying-wei Ai (Science of The Total Environment, 2023)

Contribution identification of hydrolyzed products of potassium ferrate on promoting short-chain fatty acids production from waste activated sludge - Cong-Cong Tang; Min Zhang; Bo Wang; Zheng-Shuo Zou; Xing-Ye Yao; Ai-Juan Zhou; Wenzong Liu; Yong-Xiang Ren; Zhi-Hua Li; Aijie Wang; Zhang-Wei He (Journal of Environmental Management, 2023)

A tumor microenvironment responsive titanium-based nanosonosensitizer for combination sonodynamic-immunotherapy with calcium ion overload - Cong Tang; Huansong Li; Mashiti Sha; Jianyin Song; Xue Bai; Kairui Liu; Yangsui Liu; Bo Yuan; Jun Yan; Jin Chang; Jun Kang (Chemical Engineering Journal, 2023)

Plant image recognition with deep learning: A review - Ying Chen; Yiqi Huang; Zizhao Zhang; Zhen Wang; Bo Liu; Conghui Liu; Cong Huang; Shuangyu Dong; Xuejiao Pu; Fanghao Wan; Xi Qiao; Wanqiang Qian (Computers and Electronics in Agriculture, 2023)

Association between PM2.5 exposure and the outcomes of ART treatment: A prospective birth cohort study - Yifan Wang; Yun Qiu; Bo Huang; Jiangbo Du; Liya Liu; Tao Jiang; Yangqian Jiang; Hong Lv; Qun Lu; Rui Qin; Shiyao Tao; Lei Huang; et al. (Science of The Total Environment, 2023)

Activation of Cannabinoid Receptor 1 in GABAergic Neurons in the Rostral Anterior Insular Cortex Contributes to the Analgesia Following Common Peroneal Nerve Ligation - Ming Zhang; Cong Li; Qian Xue; Chang-Bo Lu; Huan Zhao; Fan-Cheng Meng; Ying Zhang; Sheng-Xi Wu; Yan Zhang; Hui Xu (Neuroscience Bulletin, 2023)
The rostral agranular insular cortex (RAIC) has been associated with pain modulation. Although the endogenous cannabinoid system (eCB) has been shown to regulate chronic pain, the roles of eCBs in the RAIC remain elusive under the neuropathic pain state. Neuropathic pain was induced in C57BL/6 mice by common peroneal nerve (CPN) ligation. The roles of the eCB were tested in the RAIC of ligated CPN C57BL/6J mice, glutamatergic, or GABAergic neuron cannabinoid receptor 1 (CB1R) knockdown mice with the whole-cell patch-clamp and pain behavioral methods. The E/I ratio (amplitude ratio between mEPSCs and mIPSCs) was significantly increased in layer V pyramidal neurons of the RAIC in CPN-ligated mice. Depolarization-induced suppression of inhibition but not depolarization-induced suppression of excitation in RAIC layer V pyramidal neurons were significantly increased in CPN-ligated mice. The analgesic effect of ACEA (a CB1R agonist) was alleviated along with bilateral dorsolateral funiculus lesions, with the administration of AM251 (a CB1R antagonist), and in CB1R knockdown mice in GABAergic neurons, but not glutamatergic neurons of the RAIC. Our results suggest that CB1R activation reinforces the function of the descending pain inhibitory pathway via reducing the inhibition of glutamatergic layer V neurons by GABAergic neurons in the RAIC to induce an analgesic effect in neuropathic pain.

Association between long-term green space exposure and mortality in China: A difference-in-differences analysis of national data in 2000, 2010 and 2019 - Cong-Cong Li; Zhi-Cheng Du; Shu-Jun Fan; Matthew H.E. Mute Browning; Luke D. Knibbs; Michael S. Bloom; Tian-Yu Zhao; Bin Jalaludin; Joachim Heinrich; Xiao-Xuan Liu; Jia-Xin Li; Yi-Dan Zhang; et al. (Science of The Total Environment, 2023)

Spatiotemporal trends of cardiovascular disease burden attributable to ambient PM2.5 from 1990 to 2019: A global burden of disease study - Yan-Hua Liu; Ya-Cong Bo; Jie You; Shao-Fei Liu; Ming-Jing Liu; Yong-Jian Zhu (Science of The Total Environment, 2023)

Mechanism of textural properties changes of cooked chicken in early postmortem: Effect of protein degradation induced by calpain on heating shrinkage - Yunhao Ma; Ying Wang; Zhaoming Wang; Bo Chen; Yong Xie; Cheng Tang; Cong Li; Kai Zhou; Hui Zhou; Baocai Xu (Food Chemistry, 2023)

Detection of walnut oil adulterated with high-linoleic acid vegetable oils using triacylglycerol pseudotargeted method based on SFC-QTOF-MS - Jing-Jing Zhang; Yan Gao; Mei-Ling Zhao; Xiao Xu; Bo-Nan Xi; Li-Ke Lin; Jing-Yi Zheng; Bang Chen; Yu Shu; Cong Li; Yehua Shen (Food Chemistry, 2023)

Source analysis of metals in the tea plant using linear correlation analysis combined with a lead-strontium isotope tracer - Yan Cong; Rui-lian Yu; Yu Yan; Bo-sen Weng; Gong-ren Hu; Jing-wei Sun; Jian-yong Cui; YanYan; Yao-yi Huang (CATENA, 2023)

Developmental and cardiac toxicity assessment of Ethyl 3-(N-butylacetamido) propanoate (EBAAP) in zebrafish embryos - Qiang Luo; Liping Ai; Shuqiong Tang; Hua Zhang; Jinze Ma; Xiaoping Xiao; Keyuan Zhong; Guiyou Tian; Bo Cheng; Cong Xiong; Xiaobei Chen; Huiqiang Lu (Aquatic Toxicology, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

‘Biotic’ potential of the red yeast Rhodotorula mucilaginosa strain JM-01 on the growth, shell pigmentation, and immune defense attributes of the shrimp, Penaeus vannamei - Bo Wang; Yang Liu; Kai Luo; Shengkun Zhang; Cong Wei; Longbin Wang; Yanguo Qiu; Xiangli Tian (Aquaculture, 2023)

Geographic mapping with unsupervised multi-modal representation learning from VHR images and POIs - Lubin Bai; Weiming Huang; Xiuyuan Zhang; Shihong Du; Gao Cong; Haoyu Wang; Bo Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Portable smartphone-assisted ratiometric fluorescence sensor for visual detection of glucose - Xiaohui Zhang; Bo Sun; Yunyi Zhang; Qingfeng Zhang; Mahmood Hassan Akhtar; Ming Li; Yuwei Gu; Cong Yu (Analytica Chimica Acta, 2023)

Climate warming alters the relative importance of plant root and microbial community in regulating the accumulation of soil microbial necromass carbon in a Tibetan alpine meadow - Mengke Cai; Guang Zhao; Bo Zhao; Nan Cong; Zhoutao Zheng; Juntao Zhu; Xiaoqing Duan; Yangjian Zhang (Global Change Biology, 2023)
Climate warming is predicted to considerably affect variations in soil organic carbon (SOC), especially in alpine ecosystems. Microbial necromass carbon (MNC) is an important contributor to stable soil organic carbon pools. However, accumulation and persistence of soil MNC across a gradient of warming are still poorly understood. An 8‐year field experiment with four levels of warming was conducted in a Tibetan meadow. We found that low‐level (+0–1.5°C) warming mostly enhanced bacterial necromass carbon (BNC), fungal necromass carbon (FNC), and total MNC compared with control treatment across soil layers, while no significant effect was caused between high‐level (+1.5–2.5°C) treatments and control treatments. The contributions of both MNC and BNC to soil organic carbon were not significantly affected by warming treatments across depths. Structural equation modeling analysis demonstrated that the effect of plant root traits on MNC persistence strengthened with warming intensity, while the influence of microbial community characteristics waned along strengthened warming. Overall, our study provides novel evidence that the major determinants of MNC production and stabilization may vary with warming magnitude in alpine meadows. This finding is critical for updating our knowledge on soil carbon storage in response to climate warming.

Global, regional, and national burden of preterm birth attributable to ambient and household PM2.5 from 1990 to 2019: Worsening or improving? - Xiao-Xuan Liu; Shu-Jun Fan; Ya-Na Luo; Li-Xin Hu; Cong-Cong Li; Yi-Dan Zhang; Jia-Xin Li; Hui-Ling Qiu; Guang-Hui Dong; Bo-Yi Yang (Science of The Total Environment, 2023)

Hydrothermal liquefaction of soybean straw: Effect of steam explosion pretreatment and reaction media - Zhi-Cong Wang; Xiao-Ke Hou; Yi-Bo Wang; Elendu Collins; Pei-Gao Duan (Fuel, 2023)

Apoptosis-related long non-coding RNA LINC5438 of Bombyx mori promotes the proliferation of BmNPV - Peng Chen; Min Cai; Yu-Jie Feng; Cong Li; Zhan-Qi Dong; Wen-Fu Xiao; Liang Tang; Yan Zhu; Ting Tian; Bo-Yuan Deng; Min-Hui Pan; Cheng Lu (Pesticide Biochemistry and Physiology, 2023)

Genome-wide characterization of LBD transcription factors in switchgrass (Panicum virgatum L.) and the involvement of PvLBD12 in salt tolerance - Cong Guan; Bo Wu; Shu Ma; Jinhong Zhang; Xuesi Liu; Hui Wang; Jinglei Zhang; Run Gao; Huixin Jiang; Chunlin Jia (Plant Cell Reports, 2023)

Constitutive model for Ya’an mudstone based on mesoscopic breakage mechanism - Yun-yong He; Cong Chen; Fu-ming Wang; Cheng-chao Guo; Bo Xiang; Di Yu; En-long Liu; Chun Ding (Journal of Mountain Science, 2023)

Risk assessment and landslide prevention design using numerical modelling — A case study in Qingliu, China - Cong-jiang Li; Yu-xiang Hu; Nan Jiang; Hai-bo Li; Jia-wen Zhou (Journal of Mountain Science, 2023)

Biomass chemical looping gasification for syngas production using modified hematite as oxygen carriers - Cong Jiang; Xiaoyu Jin; Tingting Xu; Bo Xiao; Zhiquan Hu; Xun Wang (Journal of Environmental Sciences, 2023)

Synergism effect of low voltage electrostatic field and antifreeze agents on enhancing the qualities of frozen beef steak: Perspectives on water migration and protein aggregation - Yong Xie; Kai Zhou; Bo Chen; Sam Al-Dalali; Cong Li; Ying Wang; Zhaoming Wang; Hui Zhou; Peijun Li; Baocai Xu (Innovative Food Science & Emerging Technologies, 2023)

Biochar as a multifunctional material facilitate the organohalide remediation: A state-of-the-art review - Xueqi Chen; Bin Wu; Wenxin Yang; Guanshu Zhao; Jinglong Han; Cong Huang; Bo Sun; Aijie Wang; Zhiling Li (Chemical Engineering Journal, 2023)

Controlling factors on the charging process of oil and gas in the eastern main sub-sag of the Baiyun Sag, Zhujiang River (Pearl River) Mouth Basin - Cong Chen; Xiangtao Zhang; Guangrong Peng; Zulie Long; Baojun Liu; Xudong Wang; Puqiang Zhai; Bo Zhang (Acta Oceanologica Sinica, 2023)

Zero-valent iron loaded on N-doped biochar fabricated by one-step pyrolysis of K2FeO4 and coffee grounds as a persulfate activator for Bisphenol A degradation - Bo Jiang; Yunshu Zhang; Cong Li; Jiaqi Guo; Chunmeng Sun (Process Safety and Environmental Protection, 2023)

Risks of applying mobilising agents for remediation of arsenic-contaminated soils: Effects of dithionite–EDTA and citric acid on arsenic fractionation, leachability, oral bioavailability/bioaccessibility and speciation - Xiao-Chen Chen; Cong-Cong Yao; Ao Wang; Zeng-Di Zhang; Long-Zhao Chen; Jian-Yu Zhang; Xian-Hua Liu; Hong-Bo Li (Journal of Hazardous Materials, 2023)

Preparation of polyethyleneimine-modified chitosan/Ce-UIO-66 composite hydrogel for the adsorption of methyl orange - Zhi Chen; Zhi-Bo Zhang; Jun Zeng; Zhi-Jie Zhang; Shan Ma; Cong-Ming Tang; Jun-Qiang Xu (Carbohydrate Polymers, 2023)

Local and Global Abnormalities in Pre-symptomatic Huntington’s Disease Revealed by 7T Resting-state Functional MRI - Juan-Juan Xie; Xiao-Yan Li; Yi Dong; Cong Chen; Bo-Yi Qu; Shuang Wang; Han Xu; Anna Wang Roe; Hsin-Yi Lai; Zhi-Ying Wu (Neuroscience Bulletin, 2023)

Understanding the mechanisms of zeolite in inhibiting Pb accumulation in different rice cultivars (Oryza sativa) - Jingxia Guo; Miaofen Chen; Yongxin Huang; Shengcong Xie; Cong Hu; Bo Xu; Guo Wang (Environmental Science and Pollution Research, 2022)

Identification of proline-rich protein 11 as a major regulator in mouse spermatogonia maintenance via an increase in BMI1 protein stability - Jiajia Xue; Tiantian Wu; Chao Huang; Minghua Shu; Cong Shen; Bo Zheng; Jinxing Lv (Molecular Biology Reports, 2022)

Preliminary analysis of a landslide-dammed lake induced by two consecutive earthquakes on June 1, 2022, Sichuan Province, China - Nan Jiang; Cong-jiang Li; Hai-bo Li; Zhi-dong Zhou; Gong-da Lu; Jia-wen Zhou (Landslides, 2022)

Construction of a core germplasm bank of upland cotton (Gossypium hirsutum L.) based on phenotype, genotype and favorable alleles - Peng Han; Xiaomin Tian; Ying Wang; Cong Huang; Yizan Ma; Xiaofeng Zhou; Yu Yu; Dawei Zhang; Haijiang Xu; Yang Cao; Bo Zhu; Zhenxiu Feng; et al. (Genetic Resources and Crop Evolution, 2022)

Mechanism of progressive failure of a slope with a steep joint under the action of freezing and thawing: model test - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Bo Lu; Xiao-ke Shen; Xiao-wei Wang; Jie-sheng Liu; Liang-liang Wu; Xin-zhou Zhang (Journal of Mountain Science, 2022)

Stabilization of coarse-grained saline soil using microbially enhanced calcium carbonate deposition - Shengyi Cong; Liang Tang; Bo Wang; Xianzhang Ling; Lin Geng; Wenqiang Xing (Bulletin of Engineering Geology and the Environment, 2022)

Syntaxin binding protein 2 in sertoli cells regulates spermatogonial stem cell maintenance through directly interacting with connexin 43 in the testes of neonatal mice - Yibo Wu; Cong Shen; Tiantian Wu; Xiaoyan Huang; Hong Li; Bo Zheng (Molecular Biology Reports, 2022)

Global patterns of soil gross immobilization of ammonium and nitrate in terrestrial ecosystems - Ahmed S. Elrys; Zhaoxiong Chen; Jing Wang; Yves Uwiragiye; Ayman M. Helmy; El‐Sayed M. Desoky; Yi Cheng; Jin‐bo Zhang; Zu‐cong Cai; Christoph Müller (Global Change Biology, 2022)
Microbial nitrogen (N) immobilization, which typically results in soil N retention but based on the balance of gross N immobilization over gross N production, affects the fate of the anthropogenic reactive N. However, global patterns and drivers of soil gross immobilization of ammonium (I NH4 ) and nitrate (I NO3 ) are still only tentatively known. Here, we provide a comprehensive analysis considering gross N production rates, soil properties, and climate and their interactions for a deeper understanding of the patterns and drivers of I NH4 and I NO3 . By compiling and analyzing 1966 observations from 274 15 N‐labelled studies, we found a global average of I NH4 and I NO3 of 7.41 ± 0.72 and 2.03 ± 0.30 mg N kg −1 day −1 with a ratio of I NO3 to I NH4 (I NO3 :I NH4 ) of 0.79 ± 0.11. Soil I NH4 and I NO3 increased with increasing soil gross N mineralization (GNM) and nitrification (GN), microbial biomass, organic carbon, and total N and decreasing soil bulk density. Our analysis revealed that GNM and GN were the main stimulators for I NH4 and I NO3 , respectively. The structural equation modeling showed that higher soil microbial biomass, total N, pH, and precipitation stimulate I NH4 and I NO3 through enhancing GNM and GN. However, higher temperature and soil bulk density suppress I NH4 and I NO3 by reducing microbial biomass and total N. Soil I NH4 varied with terrestrial ecosystems, being greater in grasslands and forests, which have higher rates of GNM, than in croplands. The highest I NO3 :I NH4 was observed in croplands, which had higher rates of GN. The global average of GN to I NH4 was 2.86 ± 0.31, manifesting a high potential risk of N loss. We highlight that anthropogenic activities that influence soil properties and gross N production rates likely interact with future climate changes and land uses to affect soil N immobilization and, eventually, the fate of the anthropogenic reactive N.

The plasminogen receptor directs maintenance of spermatogonial stem cells by targeting BMI1 - Hui Zhou; Cong Shen; Yueshuai Guo; Xiaoyan Huang; Bo Zheng; Yibo Wu (Molecular Biology Reports, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Age, origin and tectonic implications of Late Carboniferous-Early Permian felsic magmatic rocks from central Inner Mongolia, south-eastern Central Asian Orogenic Belt - Jianzhou Tang; Jian Cheng; Zhicheng Zhang; Jinzhuang Xue; Bo Liu; Tiejun Duan; Weijia Zhan; Cong Ding; Qi Wang; Huaihui Zhang; Yunxi Meng (International Geology Review, 2022)

Dynamic evolution mechanism and subsequent reactivated ancient landslide analyses of the “6.17” Danba sequential disasters - Nan Jiang; Hai-bo Li; Yu-xiang Hu; Jie-yuan Zhang; Wei Dai; Cong-jiang Li; Jia-wen Zhou (Bulletin of Engineering Geology and the Environment, 2022)

Recycling of supra-crustal materials in the rhyolites from north Sonid Youqi: implications for the crustal evolution in the southeast Central Asian Orogenic Belt - Jian-Zhou Tang; Zhicheng Zhang; Bo Liu; Shaohua Zhang; Ke Li; Qi Wang; Cong Ding (International Journal of Earth Sciences, 2022)

Geochronology, geochemistry and zircon Hf isotope constraints on petrogenesis and tectonic setting of Early Permian volcanic rocks from Sonid Youqi area, Solonker Zone - Jianzhou Tang; Zhicheng Zhang; Bo Liu; Qi Wang; Cong Ding (International Geology Review, 2022)

Petrogenesis of the Late Triassic Mengsong strongly peraluminous granites in the southeastern Tibetan Plateau: highly fractionated from crystal mush - Feng Cong; Fu-Yuan Wu; Wen-Chang Li; De-Feng He; Zai-Bo Sun; Xiao-Ming Huang; Zhi-Zhong Hu; Han Zhao (International Geology Review, 2022)

Estimate greenhouse gas emissions from water-saving and drought-resistance rice paddies by deNitrification-deComposition model - Xianxian Zhang; Huifeng Sun; Junguo Bi; Bo Yang; Jining Zhang; Cong Wang; Sheng Zhou (Clean Technologies and Environmental Policy, 2022)

Characteristics and Environmental Response of White Secondary Mineral Precipitate in the Acid Mine Drainage From Jinduicheng Mine, Shaanxi, China - Cong Lu; Bo Yang; Xing Cui; Sichang Wang; Chengtun Qu; Weiwei Zhang; Bo Zhou (Bulletin of Environmental Contamination and Toxicology, 2021)

Global gross nitrification rates are dominantly driven by soil carbon‐to‐nitrogen stoichiometry and total nitrogen - Ahmed S. Elrys; Jing Wang; Mohamed A. S. Metwally; Yi Cheng; Jin‐Bo Zhang; Zu‐Cong Cai; Scott X. Chang; Christoph Müller (Global Change Biology, 2021)
Soil gross nitrification (GN) is a critical process in the global nitrogen (N) cycle that results in the formation of nitrate through microbial oxidation of ammonium or organic N, and can both increase N availability to plants and nitrous oxide emissions. Soil GN is thought to be mainly controlled by soil characteristics and the climate, but a comprehensive analysis taking into account the climate, soil characteristics, including microbial characteristics, and their interactions to better understand the direct and indirect controlling factors of GN rates globally is lacking. Using a global meta‐analysis based on 901 observations from 330 15 N‐labeled studies, we show that GN differs significantly among ecosystem types, with the highest rates found in croplands, in association with higher pH which stimulates nitrifying bacteria activities. Autotrophic and heterotrophic nitrifications contribute 63% and 37%, respectively, to global GN. Soil GN increases significantly with soil total N, microbial biomass, and soil pH, but decreases significantly with soil carbon (C) to N ratio (C:N). Structural equation modeling suggested that GN is mainly controlled by C:N and soil total N. Microbial biomass and pH are also important factors controlling GN and their effects are similar. Precipitation and temperature affect GN by altering C:N and/or soil total N. Soil total N and temperature drive heterotrophic nitrification, whereas C:N and pH drive autotrophic nitrification. Moreover, GN is positively related to nitrous oxide and carbon dioxide emissions. This synthesis suggests that changes in soil C:N, soil total N, microbial population size, and/or soil pH due to anthropogenic activities may influence GN, which will affect nitrate accumulation and gaseous emissions of soils under global climate and land‐use changes.

Numerical estimation of landslide-generated waves at Kaiding Slopes, Houziyan Reservoir, China, using a coupled DEM-SPH method - Yu-xiang Hu; Yong-guo Zhu; Hai-bo Li; Cong-jiang Li; Jia-wen Zhou (Landslides, 2021)

Lipidomic analyses reveal enhanced lipolysis in planthoppers feeding on resistant host plants - Xiaohong Zheng; Yeyun Xin; Yaxin Peng; Junhan Shan; Ning Zhang; Di Wu; Jianping Guo; Jin Huang; Wei Guan; Shaojie Shi; Cong Zhou; Rongzhi Chen; et al. (Science China Life Sciences, 2021)

Temperature changes between neighboring days and childhood asthma: a seasonal analysis in Shanghai, China - Xiaoning Lei; Lijuan Liu; Renjie Chen; Cong Liu; Jianguo Hong; Lanfang Cao; Yanming Lu; Xiaoyan Dong; Xinchang Chen; Xiangwei Qiu; Min Xia; Bo Ding; et al. (International Journal of Biometeorology, 2021)

Design and Characterization of a Novel Hybrid Antimicrobial Peptide OM19R Based on Oncocin and MDAP-2 - Lei Liu; Jie Liu; Qi Cui; Bo-Yan Jia; Zhi-Hua Pei; Kokou Ayefounin Odah; Yi-Ming Wang; Wen-Long Dong; Ling-Cong Kong; Hong-Xia Ma (International Journal of Peptide Research and Therapeutics, 2020)

Model test of the stability degradation of a prestressed anchored rock slope system in a corrosive environment - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Zhi-jun Liu; Bo Lu; Bin Wang; Yu-zhou Jiang; Jie-sheng Liu; Ping Zeng (Journal of Mountain Science, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Prenatal di-(2-ethylhexyl) phthalate maternal exposure impairs the spatial memory of adult mouse offspring in a phase- and gender-dependent manner - Ling-Li Zhao; Ru Shen; Cong-Cong Sun; Shan-Yu Zhang; Bo Wang; Mei-Fang Sun; De-Xiang Xu (Environmental Science and Pollution Research, 2020)

Correction to: Emodin alleviated pulmonary inflammation in rats with LPS-induced acute lung injury through inhibiting the mTOR/HIF-1α/VEGF signaling pathway - Xiaoqian Li; Cong Shan; Zhonghua Wu; Hongji Yu; Aidong Yang; Bo Tan (Inflammation Research, 2020)

Preparation of aluminum sludge composite gel spheres and adsorption of U(IV) from aqueous solution - Jin-hui Yang; Zeng-jiang Lei; Yang-hong Dai; Yi Luo; Shui-bo Xie; Jing-song Wang; Shu-kui Zhou; Bai Wei; Cong Li; Shi-qing Hu (Environmental Science and Pollution Research, 2020)

Deformation characteristics and failure mechanism of a reactivated landslide in Leidashi, Sichuan, China, on August 6, 2019: an emergency investigation report - Weile Li; Bo Zhao; Qiang Xu; Fan Yang; Hao Fu; Cong Dai; Xinxin Wu (Landslides, 2020)

Emodin alleviated pulmonary inflammation in rats with LPS-induced acute lung injury through inhibiting the mTOR/HIF-1α/VEGF signaling pathway - Xiaoqian Li; Cong Shan; Zhonghua Wu; Hongji Yu; Aidong Yang; Bo Tan (Inflammation Research, 2020)

ABA and sucrose co-regulate strawberry fruit ripening and show inhibition of glycolysis - Ya Luo; Cong Ge; Yajie Ling; Fan Mo; Min Yang; Leiyu Jiang; Qing Chen; Yuanxiu Lin; Bo Sun; Yong Zhang; Yan Wang; Mengyao Li; et al. (Molecular Genetics and Genomics, 2020)

Tea Residue Boosts Dye Decolorization and Induces the Evolution of Bacterial Community - Xuehui Xie; Xiulin Zheng; Chengzhi Yu; Qingyun Zhang; Yiqin Wang; Junhao Cong; Na Liu; Zhenjiang He; Bo Yang; Jianshe Liu (Water, Air, & Soil Pollution, 2019)

Antimicrobial susceptibility and molecular typing of Pasteurella multocida isolated from six provinces in China - Ling-Cong Kong; Zi Wang; Yi-Ming Wang; Wen-Long Dong; Bo-Yan Jia; Duo Gao; Xiu-Yun Jiang; Hong-Xia Ma (Tropical Animal Health and Production, 2019)

Confluentibacter flavum sp. nov., Isolated from the Saline Lake - Yu. Li; Xin-Jun Hou; Xia Shen; Shuai-Bo Han; Zhao Ju; Zhe Zhao; Xiao-Yun Yu; Min Wu; Cong Sun (Current Microbiology, 2018)

Restoration of SMN expression in mesenchymal stem cells derived from gene-targeted patient-specific iPSCs - Mai Feng; Cong Liu; Yan Xia; Bo Liu; Miaojin Zhou; Zhuo Li; Qianru Sun; Zhiqing Hu; Yanchi Wang; Lingqian Wu; Xionghao Liu; Desheng Liang (Journal of Molecular Histology, 2018)

Simulated nitrogen deposition significantly suppresses the decomposition of forest litter in a natural evergreen broad-leaved forest in the Rainy Area of Western China - Shi-xing Zhou; Cong-de Huang; Bo-han Han; Yong-xiang Xiao; Jian-dong Tang; Yuan-bin Xiang; Chao Luo (Plant and Soil, 2017)

Effect of Chitosan Coating Enriched with 6-gingerol on Red Drum Fillets Quality and Shelf Life during Refrigerated Storage - Hongbo Mi; Bo Zhao; Cong Wang; Yongxia Xu; Yongjun Ma; Linchun Mao; Jianrong Li (Journal of Aquatic Food Product Technology, 2017)

Taxanes from Taxus wallichiana var. mairei cultivated in the southern area of the Yangtze River in China - Bo-Shu Lun; Li-Wei Shao; Yong Wang; Cong-Cong Li; Hua Yu; Chun-Hua Wang; Yan Zhu (Natural Product Research, 2017)

Position and Angular Misalignment Analysis for Implantable Wireless Power Transfer System Based on Magnetic Resonance - Fei-Xiang Gong; Zhiqiang Wei; Haokun Chi; Bo Yin; Ying Sun; Yanping Cong; Mingui Sun (Journal of Medical and Biological Engineering, 2017)

Seasonal variations of organic carbon and nitrogen in the upper basins of Yangtze and Yellow Rivers - Xiang-ying Li; Yong-jian Ding; Tian-ding Han; Jian-zhong Xu; Shi-chang Kang; Qing-bai Wu; Mika Sillanpää; Zhong-bo Yu; Cong-rong Yu (Journal of Mountain Science, 2017)

Dimeric furanocoumarins from the roots of Angelica dahurica - Wan-Qing Yang; Zhi-Xiang Zhu; Yue-Lin Song; Bo-Wen Qi; Juan Wang; Cong Su; Peng-Fei Tu; She-Po Shi (Natural Product Research, 2017)

Age-dependent impact of inferior alveolar nerve transection on mandibular bone metabolism and the underlying mechanisms - Qingqing Wu; Bo Yang; Cong Cao; Mengkai Guang; Ping Gong (Journal of Molecular Histology, 2016)

Neuroprotective effects of a chromatin modifier on ischemia/reperfusion neurons: implication of its regulation of BCL2 transactivation by ERα signaling - Jun Guo; Tao Zhang; Jia Yu; Hong-Zeng Li; Cong Zhao; Jing Qiu; Bo Zhao; Jie Zhao; Wei Li; Tian-Zhi Zhao (Cell and Tissue Research, 2016)

Enhanced short-cut nitrification in an airlift reactor by CaCO3 attachment on biomass under high bicarbonate condition - Mohammad Ali; Li-Yuan Chai; Hai-Ying Wang; Chong-Jian Tang; Xiao-Bo Min; Xu Yan; Cong Peng; Yu-Xia Song; Ping Zheng (Biodegradation, 2016)

Astragalus Polysaccharide Inhibits Autophagy and Apoptosis from Peroxide-Induced Injury in C2C12 Myoblasts - Yi Yin; Lu Lu; Dongtao Wang; Ying Shi; Ming Wang; Yanfeng Huang; Dexiu Chen; Cong Deng; Jiebin Chen; Peijia Lv; Yanjing Wang; Chengjie Li; et al. (Cell Biochemistry and Biophysics, 2015)

Control of soil-borne pathogen Fusarium oxysporum by biological soil disinfestation with incorporation of various organic matters - Xin Qi Huang; Teng Wen; Jin Bo Zhang; Lei Meng; Tong Bin Zhu; Liang Liang Liu; Zu Cong Cai (European Journal of Plant Pathology, 2015)

Age, petrogenesis and tectonic significance of the ferrobasalts in the Chagangnuoer iron deposit, western Tianshan - Ning-Bo Li; He-Cai Niu; Xing-Chun Zhang; Qiao-Song Zeng; Qiang Shan; Cong-Ying Li; Shuang Yan; Wu-Bin Yang (International Geology Review, 2015)

What are the effects of aromatic plants and meteorological factors on Pseudococcus comstocki and its predators in pear orchards? - Hui Hua Wan; Bei Zhou Song; Guang Bo Tang; Jie Zhang; Yun Cong Yao (Agroforestry Systems, 2015)

An inverse approach to identifying the in vivo material parameters of female pelvic floor muscles using MRI data - RuiWen Yao; Le Du; Lan Zhu; ZhiHai Xiang; Cong Chen; Bo Hou; Feng Feng (Science China Life Sciences, 2015)

Trace levels of mitomycin C disrupt genomic integrity and lead to DNA damage response defect in long-term-cultured human embryonic stem cells - Di Zhou; Ge Lin; Si-Cong Zeng; Bo Xiong; Ping-Yuan Xie; De-Hua Cheng; Qing Zheng; Qi Ouyang; Xiao-Ying Zhou; Wei-Ling Tang; Yi Sun; Guang-Ying Lu; et al. (Archives of Toxicology, 2015)

Effects of soil moisture on gross N transformations and N2O emission in acid subtropical forest soils - Yi Cheng; Jing Wang; Shen-Qiang Wang; Jin-Bo Zhang; Zu-Cong Cai (Biology and Fertility of Soils, 2014)

Re-Transurethral Resection Treatment for Non-invasive Bladder Tumor - Cong-hui Han; Zhenduo Shi; Xujun Xuan; Bo Chen; Bingzheng Dong; Lin Hao; Xiangzheng Qiu; Xiangju Zhou; Tian-lin Wu; Dong Liu (Cell Biochemistry and Biophysics, 2014)

Comparative proteome analysis of the response of ramie under N, P and K deficiency - Gang Deng; Li Jun Liu; Xin Yue Zhong; Cheng Ying Lao; Hong Yang Wang; Bo Wang; Cong Zhu; Fahad Shah; Ding Xiang Peng (Planta, 2014)

The mechanisms behind reduced NH4 + and NO3 − accumulation due to litter decomposition in the acidic soil of subtropical forest - Yi Cheng; Jing Wang; Jin-Bo Zhang; Bruno Mary; Zu-Cong Cai (Plant and Soil, 2014)

A systematic proteomic analysis of NaCl-stressed germinating maize seeds - Ling-Bo Meng; Yi-Bo Chen; Tian-Cong Lu; Yue-Feng Wang; Chun-Rong Qian; Yang Yu; Xuan-Liang Ge; Xiao-Hui Li; Bai-Chen Wang (Molecular Biology Reports, 2014)

Shapinggou: the largest Climax-type porphyry Mo deposit in China - Hong Zhang; Cong-Ying Li; Xiao-Yong Yang; Ya-Li Sun; Jiang-Hong Deng; Hua-Ying Liang; Rui-Long Wang; Bo-Hua Wang; Yu-Xian Wang; Wei-Dong Sun (International Geology Review, 2014)

Ecological risks and potential sources of heavy metals in agricultural soils from Huanghuai Plain, China - Lingli Zhou; Bing Yang; Nandong Xue; Fasheng Li; Hans Martin Seip; Xin Cong; Yunzhong Yan; Bo Liu; Baolu Han; Huiying Li (Environmental Science and Pollution Research, 2014)

Association Between Neurotensin Receptor 1 Gene Polymorphisms and Alcohol Dependence in a Male Han Chinese Population - Hui Ma; Yinglin Huang; Bo Zhang; Yuan Wang; Hong Zhao; Hong Du; Zhengtu Cong; Jingying Li; Gang Zhu (Journal of Molecular Neuroscience, 2013)

The Transurethral Seminal Vesiculoscopy in the Diagnosis and Treatment of the Seminal Vesicle Disease - Cong-hui Han; Qing Liang; Bing-zheng Dong; Lin Hao; Tao Fan; Jun-jie Zhang; Wen-da Zhang; Bo Chen; Xiang-zheng Qiu; Xiang-ju Zhou; Chang-song Pei (Cell Biochemistry and Biophysics, 2013)

Repellent and attractive effects of herbs on insects in pear orchards intercropped with aromatic plants - Guang Bo Tang; Bei Zhou Song; Ling Ling Zhao; Xu Sheng Sang; Hui Hua Wan; Jie Zhang; Yun Cong Yao (Agroforestry Systems, 2013)

Isolation and characterization of 16 polymorphic microsatellite markers for the mudskipper (Boleophthalmus pectinirostris) - Cong-Tao Wang; Zhi-Zhi Liu; Ling-Bo Ma; Jia-Mei Zhang; Zhen Zeng; An-Yuan He; Shou-Jie Tang; Wen-Qiao Tang (Conservation Genetics Resources, 2012)

Wheat straw and its biochar have contrasting effects on inorganic N retention and N2O production in a cultivated Black Chernozem - Yi Cheng; Zu-cong Cai; Scott X. Chang; Jing Wang; Jin-bo Zhang (Biology and Fertility of Soils, 2012)

Calmodulin-binding protein CBP60g is a positive regulator of both disease resistance and drought tolerance in Arabidopsis - Dongli Wan; Ruili Li; Bo Zou; Xin Zhang; Jingyu Cong; Ruigang Wang; Yiji Xia; Guojing Li (Plant Cell Reports, 2012)

A fully human CD19/CD3 bi-specific antibody triggers potent and specific cytotoxicity by unstimulated T lymphocytes against non-Hodgkin’s lymphoma - Yan Zhou; Lan-tu Gou; Bo Mu; Wei-chan Liao; Jing He; Cong Ma; Yu-qin Yao; Jin-liang Yang (Biotechnology Letters, 2012)

Differential effects of paraoxonase 1 (PON1) polymorphisms on cancer risk: evidence from 25 published studies - Dai-Hua Fang; Cong-Hai Fan; Qiang Ji; Bo-Xiang Qi; Juan Li; Lu Wang (Molecular Biology Reports, 2012)

Soil moisture effects on gross nitrification differ between adjacent grassland and forested soils in central Alberta, Canada - Yi Cheng; Zu-cong Cai; Jin-bo Zhang; Man Lang; Bruno Mary; Scott X. Chang (Plant and Soil, 2012)

Electrophysiologic Characteristics of the Crista Terminalis and Implications on Atrial Tachycardia in Rabbits - Jin Li-jun; Liu Xue-yin; Huang Cong-xin; Yang Bo; Yang Sha-ning; Wu Gang; Xie Qiang; Liu Huang-jun (Cell Biochemistry and Biophysics, 2012)

Clinical outcomes of fertility-sparing treatments in young patients with epithelial ovarian carcinoma - Jun Hu; Li-rong Zhu; Zhi-qing Liang; Yuan-guang Meng; Hong-yan Guo; Peng-peng Qu; Cai-ling Ma; Cong-jian Xu; Bi-bo Yuan (Journal of Zhejiang University-SCIENCE B, 2011)

Significant association of SNP rs2106261 in the ZFHX3 gene with atrial fibrillation in a Chinese Han GeneID population - Cong Li; Fan Wang; Yanzong Yang; Fenfen Fu; Chengqi Xu; Lisong Shi; Sisi Li; Yunlong Xia; Gang Wu; Xiang Cheng; Hui Liu; Chuchu Wang; et al. (Human Genetics, 2011)

Large-scale analysis of phosphorylated proteins in maize leaf - Ying-Dong Bi; Hong-Xia Wang; Tian-Cong Lu; Xiao-hui Li; Zhuo Shen; Yi-Bo Chen; Bai-Chen Wang (Planta, 2011)

Porphyrin and Galactosyl Conjugated Micelles for Targeting Photodynamic Therapy - De-Qun Wu; Ze-Yong Li; Cao Li; Jian-Jun Fan; Bo Lu; Cong Chang; Si-Xue Cheng; Xian-Zheng Zhang; Ren-Xi Zhuo (Pharmaceutical Research, 2010)

Assessment of association of rs2200733 on chromosome 4q25 with atrial fibrillation and ischemic stroke in a Chinese Han population - Lisong Shi; Cong Li; Chuchu Wang; Yunlong Xia; Gang Wu; Fan Wang; Chengqi Xu; Pengyun Wang; Xiuchun Li; Dan Wang; Xin Xiong; Ying Bai; et al. (Human Genetics, 2009)

Isolation of cellulose—producing microbes from the intestine of grass carp (Ctenopharyngodon idellus) - He Li; Zhang Zheng; Xie Cong-xin; Hao Bo; Wang Chao-yuan; He Gang (Environmental Biology of Fishes, 2009)

Introduction of a seedling production method using vegetative gametophytes to the commercial farming of Laminaria in China - Bo Xu; Quan Sheng Zhang; Shan Cun Qu; Yi Zhou Cong; Xue Xi Tang (Journal of Applied Phycology, 2009)

Dickkopf (Dkk) 1 promotes the differentiation of mouse embryonic stem cells toward neuroectoderm - Xiang Bo Kong; Cong Zhang (In Vitro Cellular & Developmental Biology - Animal, 2009)

A shotgun phosphoproteomics analysis of embryos in germinated maize seeds - Tian-Cong Lu; Ling-Bo Meng; Chuan-Ping Yang; Gui-Feng Liu; Guan-Jun Liu; Wei Ma; Bai-Chen Wang (Planta, 2008)

Expression of a truncated ripening inhibitor (RIN) protein from tomato and production of an anti-RIN antibody - Hong-Liang Zhu; Ben-Zhong Zhu; Ya-Li Zhang; Yi Shao; Xiao-Guang Wang; Yuan-Hong Xie; An-Jun Chen; Ying-Cong Li; Hui-Qin Tian; Yun-Bo Luo (Biotechnology Letters, 2007)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Cloning of a novel human NHEDC1 (Na+/H+ exchanger like domain containing 1) gene expressed specifically in testis - Guangming Ye; Cong Chen; Dingding Han; Xiabin Xiong; Yahui Kong; Bo Wan; Long Yu (Molecular Biology Reports, 2006)

Changes in Soil Microbial Community Associated with Invasion of the Exotic Weed, Mikania micrantha H.B.K - Wei-hua Li; Cong-bang Zhang; Hong-bo Jiang; Guo-rong Xin; Zhong-yi Yang (Plant and Soil, 2006)

Protein and hordein fraction content in barley seeds as affected by sowing date and their relations to malting quality - Jun-cong Qi; Jin-xin Chen; Jun-mei Wang; Fei-bo Wu; Lian-pu Cao; Guo-ping Zhang (Journal of Zhejiang University-SCIENCE B, 2005)